Hotel, restaurant, and travel law : a preventive approach - Cournoyer, Norman G. (Delmar Publishers, 1999)
"Hotel and restaurant owners alike will benefit from the information contained in this book. Written without legalese, it will help the user avoid lawsuits, protecting guests from unnecessary injury and the facility from financially draining litigation. A new chapter on casino law will introduce the reader to the prominent new role that casinos are playing in the hospitality industry and their effects on the law."--BOOK JACKET.